How Female Adolescents Exposed To Pornography? - Sari, Rita Kartika; Anggara, Andhika Dwi; Intan, Yulice Soraya Nur; Mayangsari, Citra Primavita; Yusuf, Iwang; Trisnadi, Setyo; Rinawati (YCAB Publisher, 2025)
Background: The digital era has markedly increased adolescents’ exposure to explicit content, including pornography, raising significant concerns regarding its impact on sexual and reproductive health. This is particularly critical among female adolescents in Indonesia, where access to comprehensive sexual education remains limited. Objective: This study aims to examine the exposure of female adolescents to pornographic content, with a focus on patterns of media consumption and their implications for reproductive health. Methods: A descriptive cross-sectional study was conducted among 58 female adolescents aged 13 to 18 years in Karanganyar, Indonesia. Data were collected using a validated questionnaire and analyzed through descriptive statistical methods to identify patterns of media usage and exposure to pornography. Results: The findings indicated that the internet and handheld devices were the predominant sources of media consumption (96.6%), significantly contributing to exposure to pornographic material (86.2% and 96.6%, respectively). Television and print media also played contributory roles, particularly through soap operas and Western films. Exposure to pornography was associated with limited awareness of reproductive health, especially among younger participants. The exposure was further linked to distorted perceptions of sexual behavior, negative body image, and potential psychological consequences such as anxiety and low self-esteem. Conclusion: This study highlights the urgent need for targeted interventions to enhance critical media literacy and provide comprehensive sexual education for adolescents. Addressing these issues is essential to mitigate the adverse effects of pornography exposure on reproductive health, while taking into account cultural and contextual factors. Future research should investigate the longitudinal effects and gender-specific outcomes to inform the development of tailored preventive strategies. Keywords: adolescents; pornography; media exposure; reproductive health; sexual education